Is Language Required to Represent Others' Mental States? Evidence From Beliefs and Other Representations. Issue 1 (7th January 2019) - Samuel, Steven; Durdevic, Kresimir; Legg, Edward W.; Lurz, Robert; Clayton, Nicola S.
Abstract: An important part of our Theory of Mind—the ability to reason about other people's unobservable mental states—is the ability to attribute false beliefs to others. We investigated whether processing these false beliefs, as well as similar but nonmental representations, is reliant on language. Participants watched videos in which a protagonist hides a gift and either takes a photo of it or writes a text about its location before a second person inadvertently moves the present to a different location, thereby rendering the belief and either the photo or text false. At the same time, participants performed either a concurrent verbal interference task (rehearsing strings of digits) or a visual interference task (remembering a visual pattern). Results showed that performance on false belief trials did not decline under verbal interference relative to visual interference. We interpret these findings as further support for the view that language does not form an essential part of the process of reasoning online ("in the moment") about false beliefs.